A comprehensive approach to sexual and transgender prejudice. Issue 3 (2nd July 2016) - Huffaker, Laena; Kwon, Paul
ABSTRACT: Prejudice and discrimination against lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals continues to have a detrimental impact on the mental health of this population. Research examining commonalities and uniqueness among negative attitudes toward specific sexual and gender minority groups is extremely limited. The authors propose that research examining sexual prejudice include attitudes toward diverse subgroups within the larger LGBTQ community in order to facilitate development of underlying constructs and identify unique contributing factors. Common and unique factors identified within existing research are organized into categorical themes, which are delineated in a conceptual factor model of sexual and transgender prejudice.